Quantitative analysis of Caffeine in the leaves and flowers of Camellia chrysantha by high-performance liquid chromatography with DAD detection - Bach, Pham Cao; Hung, Nguyen Phi; Inh, Cam Thi; Quan, Pham Minh; Toan, Tran Quoc; Minh, Pham Thi Hong; Long, Pham Quoc; Van, Nguyen Thi Hong (Vietnam Journal of Science and Technology, 2020)
Caffeine (1,3,7-trimethylxanthine) is the active alkaloid component which is a naturally occurring substance found in the leaves, seeds or fruits of over 63 plants species worldwide. Although caffeine intoxications are rare, they prove the toxic potential of this common constituent, resulting the tachycardia, atrial arrhythmias, convulsions or even coma. Caffeine toxic effect is increased when taken with other medicines, because it is metabolized through the cytochrome P450 system – primarily by the isoenzyme cYP1A2. This enzyme is also inhibited by antipsychotics and antiarrhythmic drugs, which could become toxic in presence of caffeine. This paper describes the methods for qualitative and quantitative determination of caffeine by HPLC. The results present optimal conditions for the rapid analysis of caffeine with high precision and accuracy which is suitable for its determination in the plant. The obtained results revealed that no caffeine is detected in the leaves and flowers of golden camellia (Camellia thrysantha). Thus, we may suggest that taking of golden camellia leaves and flowers as natural alternative to current decaffeinated tea could be avoid some unwanted side effects that caffeine produced beside the antioxidant content and health beneﬁts of the plant material.